NF-κB-Induced IL-6 Ensures STAT3 Activation and Tumor Aggressiveness in Glioblastoma - McFarland, Braden C.; Hong, Suk W.; Rajbhandari, Rajani; Twitty, George B.; Gray, G. Kenneth; Yu, Hao; Benveniste, Etty N.; Nozell, Susan E. (PloS one, 2013)
Glioblastoma (GBM) is the most aggressive, neurologically destructive and deadly tumor of the central nervous system (CNS). In GBM, the transcription factors NF-κB and STAT3 are aberrantly activated and associated with tumor cell proliferation, survival, invasion and chemoresistance. In addition, common activators of NF-κB and STAT3, including TNF-α and IL-6, respectively, are abundantly expressed in GBM tumors. Herein, we sought to elucidate the signaling crosstalk that occurs between the NF-κB and STAT3 pathways in GBM tumors. Using cultured GBM cell lines as well as primary human GBM xenografts, we elucidated the signaling crosstalk between the NF-κB and STAT3 pathways utilizing approaches that either a) reduce NF-κB p65 expression, b) inhibit NF-κB activation, c) interfere with IL-6 signaling, or d) inhibit STAT3 activation. Using the clinically relevant human GBM xenograft model, we assessed the efficacy of inhibiting NF-κB and/or STAT3 alone or in combination in mice bearing intracranial xenograft tumors in vivo. We demonstrate that TNF-α-induced activation of NF-κB is sufficient to induce IL-6 expression, activate STAT3, and elevate STAT3 target gene expression in GBM cell lines and human GBM xenografts in vitro. Moreover, the combined inhibition of NF-κB and STAT3 signaling significantly increases survival of mice bearing intracranial tumors. We propose that in GBM, the activation of NF-κB ensures subsequent STAT3 activation through the expression of IL-6. These data verify that pharmacological interventions to effectively inhibit the activity of both NF-κB and STAT3 transcription factors must be used in order to reduce glioma size and aggressiveness.